The fertility of ram sperm held for 24 h at 5 degrees C prior to cryopreservation - Purdy, Phillip H.; Mocé, Eva; Stobart, Robert; Murdoch, William J.; Moss, Gary E.; Larson, Brent; Ramsey, Shawn; Graham, James K.; Blackburn, Harvey D. (2017)
Diluted ram sperm can be held for 24 h at 5 °C prior to cryopreservation without impacting cryosurvival rates, however, the effects this storage has on subsequent fertility are unknown. These studies were conducted to evaluate the fertility of semen held for 24 h (to mimic shipping semen to a cryopreservation center), prior to freezing. Semen from Suffolk rams (n = 3 in experiment 1 and n = 6 in experiment 2) with initial motility of greater than 70%, were diluted to 200 × 106 sperm/mL, in one step, with a Tris–egg yolk–glycerol diluent. In experiment 1, diluted samples were cooled to 5 °C over 2 h, and then divided. Sperm in one fraction were loaded into 0.5 mL straws, frozen (T0) and stored in liquid nitrogen until thawing. Sperm in the second fraction were held at 5 °C for 24 h (T24) before being frozen. In experiment 2 ejaculates were collected and divided into two fractions. Sperm in one fraction were treated with cholesterol-loaded cyclodextrin (CLC) and sperm in the other served as control. Both fractions were diluted, cooled, and cryopreserved as described in experiment 1. Stage of the estrous cycle was synchronized in ewes (n = 196) using controlled internal drug releasing devices (CIDR) for 12 d and at CIDR removal each ewe was administered PMSG (500 IU in experiment 1 and 350 IU in experiment 2) immediately before insemination. Ewes were stratified by age and randomly assigned to one of the semen treatments; experiment 1: Fresh (F), T0, or T24; experiment 2: F, T24, or CLC, and inseminated laparoscopically 56 h after CIDR removal. Differences in fertility were detected between experiments, but not for treatments within experiments. Differences in fertility were also observed due to ewe age, with the 3-year-old ewes having the greatest fertility (50.7%) and 6-year-old ewes having the least fertility (9.6%; P < 0.05). Differences in the prolificacy rates due to semen treatment were also observed but differences due to ewe age were not detected. Therefore, sperm can be held at 5 °C for 24 h prior to cryopreservation without altering sperm fertility